2014
DOI: 10.1016/j.physbeh.2014.06.018
|View full text |Cite
|
Sign up to set email alerts
|

Early deprivation induces competitive subordinance in C57BL/6 male mice

Abstract: Rodent models have been widely used to investigate the impact of early life stress on adult health and behavior. However, the social dimension has rarely been incorporated into the analysis due to methodological limitations. This study characterized the effects of neonatal social isolation (early deprivation, ED) on adult C57BL/6 mouse behavior in a social context using our recently developed behavioral test protocols for group-housed mice. During the first two postnatal weeks, half of the pups per dam were se… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
40
0

Year Published

2015
2015
2020
2020

Publication Types

Select...
8
1
1

Relationship

1
9

Authors

Journals

citations
Cited by 55 publications
(42 citation statements)
references
References 54 publications
2
40
0
Order By: Relevance
“…We did not detect any statistically relevant enrichment-induced differences of Lsamp expression in the frontal cortex, hypothalamus, thalamus, ventral striatum, or temporal lobe. It has been shown that social isolation affects the expression level of several genes (Benner et al, 2014; Siuda et al, 2014) and Lsamp -deficient mice tend to be insensitive to separation from the group (Innos et al, 2012); isolation stress had no effect on the expression levels of Lsamp transcripts in any of the brain areas investigated in the current study.…”
Section: Discussionmentioning
confidence: 42%
“…We did not detect any statistically relevant enrichment-induced differences of Lsamp expression in the frontal cortex, hypothalamus, thalamus, ventral striatum, or temporal lobe. It has been shown that social isolation affects the expression level of several genes (Benner et al, 2014; Siuda et al, 2014) and Lsamp -deficient mice tend to be insensitive to separation from the group (Innos et al, 2012); isolation stress had no effect on the expression levels of Lsamp transcripts in any of the brain areas investigated in the current study.…”
Section: Discussionmentioning
confidence: 42%
“…For instance, adult rats that experienced repeated MD in early life showed enhanced vulnerability to stress, as demonstrated by an increase in depressive behaviors, such as a lower sucrose preference in a sucrose preference test and a longer immobility time in a forced swimming test [13]. Benner suggested that early deprivation can induce competitive subordinance and impaired reversal learning with altered functions of the limbic and frontal cortices in adult C57BL/6 mice [14]. However, the effect of MD in early life, particularly the neonatal days during which multiple neural systems are established [15,16], has rarely been investigated, which may be partially due to the lack of parameters that can be quantitatively analyzed in very young rodents.…”
Section: Introductionmentioning
confidence: 99%
“…Our study demonstrated that isolated rearing mice induced spatial and non-spatial cognitive deficits as well as abnormal work memory, which are consistent with previous published papers ( Khodaie et al, 2015). Social isolation results in cognitive dysfunction, which is also supported by the view that individual rearing has effects on impairing cognition ability on the following behavior tests (Benner et al, 2014;Green & McCormick, 2013). In the rotating T-maze, 6 weeks isolation leads to reversal-learning impairment in Wistar rats (Quan et al, 2010); C57BL/6J and DBA/2 strains reared in 7 weeks isolation since postnatal day 28 show significantly impaired fear conditioning (Võikar et al, 2005); The learning memory ability decreases in isolation-reared rats by the performance of Morris water maze and attention set shifting.…”
Section: Social Isolation-induced Cognitive Deficitssupporting
confidence: 93%